Frequency of Contact and Explanations for Increased Contact between Grandchildren and Their Grandparents during the COVID-19 Pandemic. Issue 2 (3rd April 2021) - McDarby, Meghan; Ju, Catherine H.; Carpenter, Brian D.
ABSTRACT: This study examined grandparent-grandchild contact during the COVID-19 pandemic using principles of Intergenerational Solidarity Theory as a framework. Young adults ( N = 165) completed an online survey about contact with grandparents before and during the pandemic. Participants also provided ratings of affectual solidarity toward grandparents and grandparents' physical and mental health. A subsample of participants ( n = 31) explained reasons for increased telephone contact with grandparents. Median frequency of grandchild-initiated contact with grandparents increased marginally during the pandemic, and higher ratings of affectual solidarity toward grandparents were significantly associated with increases in frequency of contact. Ratings of grandparents' physical and mental health were not significantly associated with changes in frequency of contact from before the pandemic to during the pandemic. The most common explanation for increased contact with grandparents during the pandemic reported by study participants was concern about COVID-19. Findings support Intergenerational Solidarity Theory and underscore its interaction with historical moments, including the COVID-19 pandemic.